Metabolomic profile of cacao cell suspensions growing in blue light/dark conditions with potential in food biotechnology (2019)
ABSTRACT : Theobroma cacao is a rich source of favonoid compounds, which are potent antioxidants. Flavonoids are well-known for their health benefts against cardiovascular diseases, cancer, and improvement of blood pressure. For this reason, cacao mass production has drawn the attention from the functional foods industry. Furthermore, cacao cell suspensions can be used to evaluate complex biosynthetic pathways, such as favonoids due to the homogeneity of the cell population, the unlimited availability of raw material, the high cell growth and division rates, and the reproducibility of in vitro growth conditions. However, the metabolome of cacao could be afected by exposure to light; especially shorter wavelengths such as blue light trigger targeted favonoid synthesis. Here, we provide the frst report of the metabolomic profle of cacao cell suspensions grown under white-blue and dark conditions. For this, targeted metabolomics was conducted on favonoids, including bioactive compounds such as catechin, epicatechin and proanthocyanidins (PAs). Moreover, untargeted metabolomics was performed to evaluate the response of the endogenous metabolites exposed to darkness and light. For this, unsupervised and supervised multivariate methods were used. Additionally, a chemical annotation and classifcation was conducted for the top 50 features obtained from the PLS-DA, in order to identify metabolic pathways that are associated to the light treatments. An increase of glycosylated favonoids and PAs with higher degrees of polymerization from cells grown under light compared to dark, suggested that light conditions may trigger mechanisms associated with moderate stress. Additionally, lipids, favonoids, and phytosterols increased after light treatment. The potential of cacao cell suspensions in food biotechnology is discussed, considering that the characterization and quantifcation of the cacao favonoid composition are the frst steps to evaluate the putative contribution of chocolate to human health.